Analysis of Principal Leadership with Teacher Performance - Vando Kristi Makaruku (Peneliti.net, 2023)
Identification of the dominant factors that influence student learning outcomes, aimed to find out (diagnose) the problems faced in learning so that improvements can be made to improve student learning outcomes. The selection of the most influential factors can be done using the analysis of the main components. The purpose of this study was to find out the main factors that influence junior high school students’ science learning outcomes in the Masohi city, Central Maluku Regency. The population in this study were 180 8th grade students at four junior high schools in Masohi city. The research instrument was in the form of a questionnaire to measure 8 variables compiled based on a Likert scale. Determination of the main factors that affect student learning outcomes was carried out using principal component analysis, with the assistance of SPSS software version 18.0. The results showed that in Public Islamic Junior High School 2 Masohi, the main factors influencing students' science learning outcomes were interest, motivation, infrastructure, and parents, while the second factor was teachers and peers, while in public junior high school 1, 2 and 3 Masohi, it appeared that the main factors influencing students' science learning outcomes were teachers, infrastructure, peers and parents, while the second factor was interest and motivation. Thus, it can be concluded that the main factors affecting learning outcomes in junior high schools in Masohi City are different